Evaluation of sperm fertilization capacity of large Japanese field mice (Apodemus speciosus) exposed to chronic low dose-rate radiation after the Fukushima accident. Issue 3 (September 2022) - Nihei, Kazu; Tokita, Syun; Yamashiro, Hideaki; Swee Ting, Valerie Goh; Nakayama, Ryo; Fujishima, Yohei; Kino, Yasushi; Shimizu, Yoshinaka; Shinoda, Hisashi; Ariyoshi, Kentaro; Kasai, Kosuke; Abe, Yasuyuki; et al.
Abstract: Due to the risk of bias in early developmental processes of radio-sensitive germ cells, the effects of radiation on reproductive ability remain unclear. In this study, wild large Japanese field mice ( Apodemus speciosus ) within the ex-evacuation zone of the Fukushima Daiichi Nuclear Power Plant (FDNPP) exposed to chronic low dose-rate (LDR) radiation since 2011 were examined. We analyzed the in vitro fertilization (IVF) capacity of cryopreserved A. speciosus sperm from 2012 to 2021 using interspecific zona pellucida (ZP)-free and homogenous wild mice oocytes. The radioactivity concentrations of 134 Cs and 137 Cs were 3, 460–37, 630 Bq/kg in the Fukushima wild mice. Frozen-thawed sperm showed generally normal acrosomal and nuclear morphology. No significant differences in sperm penetration rate to that of ZP-free mouse oocytes were observed between the control and Fukushima sperm. When frozen-thawed A. speciosus sperm was used for IVF, 44%–90% homogenous wild mice oocytes fertilized and developed a 2-cell embryo. This study was the first to reveal that long-term chronic LDR radiation exposure (0.18–0.59 mGy/d) associated with the FDNPP accident showed no detrimental effect on the IVF capacity of cryopreserved sperm in wild A. speciosus . This study also provides an alternative framework to estimate radiation effects on wild mice reproduction.